Inhibitory Control Training - A Multidisciplinary Approach 2020
DOI: 10.5772/intechopen.89803
|View full text |Cite
|
Sign up to set email alerts
|

When Aggression Is Out of Control: From One-Person to Two-Person Neuropsychology

Abstract: From a neuropsychological perspective, impulsive aggression and its treatment are usually conceptualized in most research as a closed executive functioning system, as though the behavior was the product of the person's cerebral functioning only. However, recent studies in social cognitive neuroscience have emphasized the influence of social factors on cognitive processes and cerebral functioning for the development and maintenance of impulsive aggression. This chapter will review studies that highlight the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Data obtained exclusively with psychiatric populations have left open the question as to whether the relationship between DMs and the decision to act aggressively in a social situation also exists in nonclinical populations. If so, decreasing the use of maladaptive DMs for adults without psychopathology may be a potential target for prevention programs of aggression and integrative models of intervention for impulsive aggression (e.g., Gagnon et al, 2019). In support of this proposal, a recent study showed that the relationship between homophobia and aggression in university students was mediated by neurotic defenses (Set and Ergin, 2020).…”
Section: Part 2: Empirical Study On Control Processes and Defense Mec...mentioning
confidence: 97%
“…Data obtained exclusively with psychiatric populations have left open the question as to whether the relationship between DMs and the decision to act aggressively in a social situation also exists in nonclinical populations. If so, decreasing the use of maladaptive DMs for adults without psychopathology may be a potential target for prevention programs of aggression and integrative models of intervention for impulsive aggression (e.g., Gagnon et al, 2019). In support of this proposal, a recent study showed that the relationship between homophobia and aggression in university students was mediated by neurotic defenses (Set and Ergin, 2020).…”
Section: Part 2: Empirical Study On Control Processes and Defense Mec...mentioning
confidence: 97%
“…Nonetheless, this study indicates that electrophysiological measurements can be more sensitive than self-report questionnaires when investigating the nature of cognitive processes associated with reactive aggression. Considering the contribution of socio-cognitive treatments that are offered to aggressive individuals (e.g., [48]), we believe that this study can help to open the way to other empirical studies using ERP tasks to understand the cognitions associated with reactive aggression among cluster B personality disorders.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that the absence of a significant relationship between the resistance to PI and the positive words can be explained by the likelihood that for individuals who are nonclinical, splitting is characterized by good and bad evaluations that are less extreme, and thus, oscillations between representations are less rapid, which makes sense given that these representations are more nuanced in terms of valence [ 57 ]. Finally, given its exploratory nature, the results of this study must be interpreted with caution and need to be replicated before concluding that they have a heuristic value, both scientifically and with regard to theoretically integrated treatment (e.g., [ 58 ]) that may be offered to individuals with symptoms of polarization and fluctuations in perception of self and others.…”
Section: Discussionmentioning
confidence: 99%